2023
DOI: 10.3390/ijms24021085
|View full text |Cite
|
Sign up to set email alerts
|

α-Crystallin Domains of Five Human Small Heat Shock Proteins (sHsps) Differ in Dimer Stabilities and Ability to Incorporate Themselves into Oligomers of Full-Length sHsps

Abstract: The α-crystallin domain (ACD) is the hallmark of a diverse family of small heat shock proteins (sHsps). We investigated some of the ACD properties of five human sHsps as well as their interactions with different full-length sHsps. According to size-exclusion chromatography, at high concentrations, the ACDs of HspB1 (B1ACD), HspB5 (B5ACD) and HspB6 (B6ACD) formed dimers of different stabilities, which, upon dilution, dissociated to monomers to different degrees. Upon dilution, the B1ACD dimers possessed the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…HSPB6 , a crucial member of the heat shock protein family B, plays a significant role in smooth muscle contraction [ 26 ]. Similar to other heat shock proteins, HSPB6 exhibits chaperone-like activity and has been shown to prevent heart failure [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSPB6 , a crucial member of the heat shock protein family B, plays a significant role in smooth muscle contraction [ 26 ]. Similar to other heat shock proteins, HSPB6 exhibits chaperone-like activity and has been shown to prevent heart failure [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…How CRYAB and the R123W variant modulate calcineurin activity, if at all, remains unclear. A recent structural study uncovered that both R120 and R123 are located in the β7–8 sheets of the crystallin domain ( 53 ). However, whereas R120 maintains solubility of CRYAB via forming salt bridges with D109 of the dimerization partner ( 53 ), R123 does not appear to participate in such activity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent structural study uncovered that both R120 and R123 are located in the β7–8 sheets of the crystallin domain ( 53 ). However, whereas R120 maintains solubility of CRYAB via forming salt bridges with D109 of the dimerization partner ( 53 ), R123 does not appear to participate in such activity. It is thus perhaps not surprising that the R123W variant did not induce protein aggregation compared to its R120G counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional studies have suggested that sHsp dimers may be the most active chaperone species; however, unraveling the complexity between structure and function for substrates remains challenging [ 1 , 5 ]. The dimer interface in the ACD of all sHsps is relatively similar in primary and secondary structure, with a canonical anti-parallel β6–β7 sheet forming the interface ( Figure 1 and Figure 7 ) [ 50 , 93 ]. The interface is stabilized by a series of salt bridges from backbone interactions and electrostatic interactions mediated by side chains [ 69 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…D109A is a mutation linked to myofibrillar myopathy pathology, and D109H has been associated with cataract and myopathy in five blood-related individuals [ 42 , 43 ]. In dimerized HspB5, D109 makes a salt bridge to R107 on the same monomer and forms hydrogen bonds with Y122 on the opposite monomer [ 15 , 71 , 93 , 98 , 100 ]. Previous work has shown that D80 interacts with both R107 and R120 to stabilize electrostatic repulsions between the arginine residues, and [ 42 ] has proposed that in the case of D109A, the R120-D80-R107 interactions were partially preserved, because alanine could not interact with R107 or Y122 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%